Pertumbuhan ikan Betok (Anabas testudineus) yang dipelihara menggunakan hapa di kolam tanah - Frid Agustinus; Infa Minggawati (Fakultas Peternakan Universitas Kristen Palangka Raya, 2019)
This research to determine the growth of Climbing Perch (Anabas testudineus) reared using hapa in soil pond. This research was conducted for one month using Climbing Perch with a size of 10-12 cm, weighing 14-18 gr. In 2 pieces of hapa with the size of hapa each 1 x 1 m in the soil pond measuring 10 x 20 m, with a stocking density of 75 ind/hapa. The results of the research showed that the survival rate of the reared fish in hapa showed a fairly good range of values of 60 %. The average weight growth at the end of the research in hapa 1 was around 24 gr and in hapa 2 it was around 23.5 gr while the specific growth rate in both hapa 1 and hapa 2 was 1.72 %/day and 1.61 %/day. While the average length growth at the end of the research in hapa 1 is around 12.5 cm and in hapa 2 is around 12.3 cm. The water quality during maintenance shows a normal range that can still be tolerated by the fish. Keywords : Growth, Climbing Perch, hapa, earthen pond.